Koperasi Syariah: Tinjauan Terhadap Kedudukan dan Peranannya dalam Pemberdayaan Ekonomi Kerakyatan - Abdullah Safe'i (Sharia and Law Faculty, 2012)
Islamic Cooperative is a cooperative finance institution run based on the principles of Sharia. Its existence is still new though, continues to increase. Islamic Cooperative or Cooperative of Islamic Financial Services is engaged in the savings and loans in the form of savings and financing earmarked for small and medium entrepreneurs. Among the legal basis is Decree of Cooperatives and Small and Medium entrepreneurship minister No. 91/Kep/M.KUKM/IX/2004 on the Implementation of Cooperatives Operations Islamic Financial Services (KJKS). Islamic cooperatives have a role in improving public welfare through financing products it offers. Its good managament can be used as an alternative of the financial institution public.